2001
DOI: 10.2307/2657108
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress, plant water status, and floral trait expression in fireweed, Epilobium angustifolium (Onagraceae)

Abstract: In a controlled environment, we artificially induced drought during flowering of Epilobium angustifolium, an animal-pollinated plant. Leaf water potential (ψ(l)) and floral traits were monitored over a 12-d period of soil moisture depletion. Soil moisture depletion induced drought stress over time, as revealed by significant treatment × day interactions for predawn and midday ψ(l). Nectar volume and flower size showed significant negative responses to drought stress, but nectar sugar concentration did not vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
165
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(184 citation statements)
references
References 71 publications
13
165
4
1
Order By: Relevance
“…These environmental factors can affect flower size variation along the gradient (Galen 2000;Knight et al 2005;Parachnowitsch & Kessler 2010). For example, Galen (2000) and Carroll et al (2001) reported negative correlations between flower size and resource availability as related to environmental stress and suggested that these negative correlations reflected the increased physiological cost of producing large flowers when resource availability is poor as a result of high environmental stress. Further study is needed to test how variations in flower dimensions might relate to variations in the abundance, diversity, and visit rate of pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…These environmental factors can affect flower size variation along the gradient (Galen 2000;Knight et al 2005;Parachnowitsch & Kessler 2010). For example, Galen (2000) and Carroll et al (2001) reported negative correlations between flower size and resource availability as related to environmental stress and suggested that these negative correlations reflected the increased physiological cost of producing large flowers when resource availability is poor as a result of high environmental stress. Further study is needed to test how variations in flower dimensions might relate to variations in the abundance, diversity, and visit rate of pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…Drought tolerant species possess adaptive traits like decrease in leaf area along with thickening, sunken stomata, increase in root length and reduction in size of flowers (Carroll et al 2001;Maroco et al 2000;Turner 1994). Current study analyzes morphological, biochemical and molecular variations in two related plant species with contrasting stress sensitivities to water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…However, plants are challenged by constantly changing abiotic and biotic environmental conditions that might affect a plant's capacity to invest in sexual reproduction (Euler and Baldwin, 1996;Carroll et al, 2001;García and Ehrlén, 2002). Besides direct impacts, like floral oviposition (Dufaÿ and Anstett, 2003) or floral herbivory (Leege and Wolfe, 2002;Rö se and Tumlinson, 2004;Theis, 2006;Sanchez-Lafuente, 2007), flowers are mostly exposed to a changing environment as part of an entirely affected plant (Sampson and Cane, 1999;Carroll et al, 2001). One of the most deleterious biotic influences on plants is green leaf herbivory.…”
mentioning
confidence: 99%